An application to the agricultural transport sector of the reliability analysis (Research, Society and Development, 2021)
Reliability analysis is the conversion of survival analysis techniques applied in the production department. To perform the reliability analysis, the data set under study must meet the necessary conditions so that it is possible to make reasonable estimates of the risk and reliability functions. The objective of this work is to use the reliability analysis, using non-parametric, semi-parametric and parametric techniques, to explore and model the time of the 11.00R22 tire. A study was carried out with the 11.00R22, and the time in kilometers traveled was calculated using an on-board computer attached to trucks. The data sets have a total of 552 tires, which differed between the three types of lifespan. In carrying out this work, the Kaplan-Meier product limit estimator was applied for the three life groups, and the log-rank test to verify the existence of a significant difference between the survival curves, both non-parametric methods, and in sequence, the parametric approach with the use of the regression model to verify which distribution suited the tire life and also the Cox model to model the risk semi-parametric approach. In the application of the methods, software R was used through the survival package. The Weibull model was best suited to model the life span of 11.00R22 tires.